Unwanted penile engorgement in pediatric patients under anesthesia: The role of anesthetic technique and other contributing factors - Hasan, Muazzam; Nadeem, Abu; Raza, Nadeem; Ahmed, Syed Moied (Indian Journal of Child Health, 2018)
Background: The mechanism behind intraoperative penile engorgement (PE) is complex. One common myth is that PE occurs more frequently during spinal anesthesia than the general anesthesia. Objective: The objective of this study was to report the incidence and management of intraoperative PE in pediatric patients undergoing urogenital operations under spinal anesthesia with or without sedation over a period of 1 year. Methods: Patients aged between 2 and 12 years, posted for elective urogenital surgery of expected duration